Community participation in rural drinking water supply and sanitation: A case study of Karnataka - Veerashekhrappa (Bangalore, 2001)
Providing safe drinking water and sanitation to the rural community is the sole responsibility of state. However, with the introduction of reforms an attempt is made to enhance private investment in this sector by involving community in all stages of development including operation and maintenance. Thus, government is changing its role from service provider to facilitator. This study finds out that community participation has enhanced private investment and identifies the constraints in operation and management.
Keywords: Drinking water; Karnataka; Sanitation